Pyomyoma as a Rare Source of Postpartum Sepsis - A. DeMaio; M. Doyle (Case Reports in Obstetrics and Gynecology)
Pyomyoma, also known as suppurative leiomyoma, is a rare clinical complication that occurs when a leiomyoma undergoes infarction and subsequent infection. A high index of suspicion is required to make the diagnosis and can be guided by a classic triad of symptoms that includes abdominal pain, sepsis without an obvious source, and a history of leiomyoma. In the vast majority of these cases, total abdominal hysterectomy is required to avoid severe morbidity and potential mortality. We present an unusual case of a postpartum pyomyoma that was successfully treated without the need for hysterectomy. With strong clinical suspicion, early diagnosis, and appropriate management, some affected patients may preserve fertility.